The Temperature-Regulation of Pseudomonas aeruginosa cmaX-cfrX-cmpX Operon Reveals an Intriguing Molecular Network Involving the Sigma Factors AlgU and SigX - Bouffartigues, Emeline; Si Hadj Mohand, Ishac; Maillot, Olivier; Tortuel, Damien; Omnes, Jordane; David, Audrey; Tahrioui, Ali; Duchesne, Rachel; Azuama, Cecil Onyedikachi; Nusser, Michael; Brenner-Weiss, Gerald; Bazire, Alexis; et al. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is a highly adaptable Gram-negative opportunistic pathogen, notably due to its large number of transcription regulators. The extracytoplasmic sigma factor (ECF sigma) AlgU, responsible for alginate biosynthesis, is also involved in responses to cell wall stress and heat shock via the RpoH alternative sigma factor. The SigX ECF sigma emerged as a major regulator involved in the envelope stress response via membrane remodelling, virulence and biofilm formation. However, their functional interactions to coordinate the envelope homeostasis in response to environmental variations remain to be determined. The regulation of the putative cmaX-cfrX-cmpX operon located directly upstream sigX was investigated by applying sudden temperature shifts from 37°C. We identified a SigX- and an AlgU- dependent promoter region upstream of cfrX and cmaX, respectively. We show that cmaX expression is increased upon heat shock through an AlgU-dependent but RpoH independent mechanism. In addition, the ECF sigma SigX is activated in response to valinomycin, an agent altering the membrane structure, and up-regulates cfrX-cmpX transcription in response to cold shock. Altogether, these data provide new insights into the regulation exerted by SigX and networks that are involved in maintaining envelope homeostasis.